2006
DOI: 10.1159/000090917
|View full text |Cite
|
Sign up to set email alerts
|

Early Catheter Removal following Transurethral Prostatectomy: A Study of 431 Patients

Abstract: Objectives: To assess and review catheter removal on the first day after transurethral prostatectomy. Subjects and Methods: The study included 431 consecutive patients who underwent transurethral prostatectomy between 2000 and 2003 at a Scarborough General Hospital, Toronto, Canada. The equipment used was a standard resectoscope with a regular loop. No roller ball or other gadget was used. The cutting and coagulation electrical variables were standard at 160 and 60 W for the generator used. The decision to rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
(23 reference statements)
1
13
0
Order By: Relevance
“…It could be argued, however, that managed care pathways are shortening hospital stay for all procedures, including transurethral resection of prostate, and in consequence the cost saving for patients and healthcare providers may be small. 6 Strengths and limitations of the review We have used the best available methods to identify, review, and meta-analyse data available to us. Several limitations must be noted, however, when interpreting the results of this review.…”
Section: Discussionmentioning
confidence: 99%
“…It could be argued, however, that managed care pathways are shortening hospital stay for all procedures, including transurethral resection of prostate, and in consequence the cost saving for patients and healthcare providers may be small. 6 Strengths and limitations of the review We have used the best available methods to identify, review, and meta-analyse data available to us. Several limitations must be noted, however, when interpreting the results of this review.…”
Section: Discussionmentioning
confidence: 99%
“…However, no study that analyzed risk factors in patients whose urethral catheters were not removed on postoperative day 1 has previously been reported. In the case of TURP, Nakagawa and Toguri [14] suggested risk factors such as age, postoperative bleeding, and several comorbidities, including coronary heart disease, renal insufficiency, and Alzheimer's disease. Das Bhagia et al [15] reported that a history of acute urinary retention does not affect the duration of catheter indwelling after the TURP procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Besides adequate urination, absence of clots and clear urine colour they considered catheter removal criteria to be normal vital findings. Catheters were removed the following day in 93.6% of patients meeting these criteria and they concluded that this approach was not only safe but also cost effective, without resulting in morbidity (9). A general assessment of available literature suggests that urologists endeavour to remove catheters in the earliest possible time.…”
Section: Discussionmentioning
confidence: 99%